The economics of climate change: Green growth, zero- or de-growth - Jan Priewe (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2021)
The article discusses the ongoing green transition towards climate neutrality in 2050 with a focus on the options of green growth, zero- or de-growth. First, the key facts about the greenhouse effect and the status quo are shown with special attention to the industrialisation of emerging economies as the key contributors to greenhouse gas emissions since about 1980. Second, the features and policies for facilitating the transition are analysed. The carbon price emerges as a key global price that needs public rather than market control. Third, the core debates on the feasibility of economic growth in ecological economics are used to shed more light on the present issues at stake. Finally, the quest for moderate global green growth is confirmed in order to accomplish decarbonization of the planet and terminate extractive capitalism as far as fossil energy is concerned; however, these attempts cannot evade the finiteness of natural resources, including land and renewable resources. The green transition leads likely close to global zero-growth of GDP which would eventually terminate the age of capital accumulation, the heart of capitalism.
Keywords: O47; P18; P28; P47; Q01; 330; growth theory; energy economics; decarbonisation; zero-growth; de-growth; climate change; carbon prices; capitalism